Well-Being in a Foreign Land: A Study of Foreign Students from Outside Java - Putri, Siskal Idzni; Kumalasari, Asteria Devy; Agustiani, Hendriati (Psyche 165 Journal, 2025)
Students who travel to study education Far from area origin often face challenges and pressure alone . Challenge is not only in the realm of academic , will but also their obligation to complete all his needs in a way independent . This condition can affect welfare psychological problems in students from out of town . It is not uncommon impact from pressure The psychological problems experienced by these students from other regions have been reported in the media and scientific studies . Although this is a phenomena that are often encountered in everyday life , but deepening about dynamics welfare psychology of migrant students in a way qualitative Still limited . This study aims to explore description welfare psychology of students from out of town based on six dimensions : self -acceptance , relationships positive with others, autonomy , mastery environment , goals in life , and personal growth . Data collection was carried out through interview method . As many as four informants from out-of- town students level bachelor from college high in West Java selected through purposive sampling . The research results describe themes specifics found​ from statements respondents . Some of these important themes including : self - acceptance advantages and disadvantages of adapting and do n't compare situations material show self -acceptance of students from out of town , communication as an important aspect in establishing Good relations overseas , determine own decision without put aside other people's views show autonomy , self -control in controlling many activity as a form mastery environment , establishing relations abroad to determine​ future career , and challenges or new experiences abroad can encourage you self -development . This study also found several factors that can play a role in the dimensions certain from welfare psychology of students living away from home .